A comparison between perpendicular and parallel plating methods for distal humerus fractures: A meta-analysis of randomized controlled trials. Issue 23 (5th June 2020) - Wang, Xiaohan; Liu, Guoyan
Abstract: Objective: To compare the clinical outcomes of perpendicular and parallel plating for the treatment of distal humerus fractures. Methods: Two investigators independently searched PubMed, OVID, and ScienceDirect databases prior to April 2019, without any limitations on language or publication status. The outcomes were union time, range of motion of elbow, Mayo Elbow Performance Score, and postoperative complications. Two authors independently performed a methodological quality and risk of bias assessment using Cochrane collaboration's tool. Data analysis was performed with STATA version 13.0. Results: Six randomized controlled trials with 305 participants were included. The present meta-analysis indicated that orthogonal plating was associated with a longer union time compared with parallel plating. There were no significant differences between the 2 groups regarding Elbow function, Mayo Elbow Performance Score, operation time, reduction quality, or postoperative complications. Conclusion: Both parallel plating and orthogonal plating are considered to be effective methods when treating distal humerus fractures. The results of this study found that parallel plating is superior to orthogonal plating in humerus fracture healing.